2021
DOI: 10.1007/s40037-021-00694-5
|View full text |Cite
|
Sign up to set email alerts
|

How preceptors develop trust in continuity clinic residents and how trust influences supervision: A qualitative study

Abstract: Introduction To advance in their clinical roles, residents must earn supervisors’ trust. Research on supervisor trust in the inpatient setting has identified learner, supervisor, relationship, context, and task factors that influence trust. However, trust in the continuity clinic setting, where resident roles, relationships, and context differ, is not well understood. We aimed to explore how preceptors in the continuity clinic setting develop trust in internal medicine residents and how trust inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…For instance, ignoring barriers to care in the moment, such as food insecurity, will hamper residents' learning and indicate that this is not an important area of concern for patient care. As seen from this work, relationships and point-of-care learning with their supervisors is critical to residents' learning, so faculty development regarding socially complex patients is critical [33,34]. These findings suggest that either the system needs to be aligned with the experience of training or we, as medical educators, need to align our learning environments to the system.…”
Section: Discussionmentioning
confidence: 84%
“…For instance, ignoring barriers to care in the moment, such as food insecurity, will hamper residents' learning and indicate that this is not an important area of concern for patient care. As seen from this work, relationships and point-of-care learning with their supervisors is critical to residents' learning, so faculty development regarding socially complex patients is critical [33,34]. These findings suggest that either the system needs to be aligned with the experience of training or we, as medical educators, need to align our learning environments to the system.…”
Section: Discussionmentioning
confidence: 84%
“…Although some studies found that resident satisfaction with CC increased with the change to an X + Y schedule, Jantea et al identified that residents’ satisfaction and stress levels at one program did not improve 17 . These studies identified several facets of CC training that predicted satisfaction, including patient characteristics, preceptor quality, and clinic operations 18 . Notably, none of these studies focus on residents’ personal experiences with CC compared with their inpatient IM rotations, and this is of interest because it is unclear whether these factors influence the decision to pursue a career in primary care.…”
mentioning
confidence: 99%
“…17 These studies identified several facets of CC training that predicted satisfaction, including patient characteristics, preceptor quality, and clinic operations. 18 Notably, none of these studies focus on residents' personal experiences with CC compared with their inpatient IM rotations, and this is of interest because it is unclear whether these factors influence the decision to pursue a career in primary care. Understanding differences in residents' perception of training in these settings can shed light on reasons that IM residents are preferentially pursuing careers in inpatient general IM.…”
mentioning
confidence: 99%